Turkish Validity and Reliability of the Quality Nursing Care Scale (QNCS-T) (Bangladesh Journal of Medical Science, 2024)
Objective: Nursing  care  is  a  unique  and  indispensable  concept  for nursing  that  includes  helping  to  meet  the  needs  of  an individual or a group of individuals offered by nurses. This study is aimed to test the validity and reliability of the Turkish version of the Quality Nursing Care Scale (QNCS-T).Materials and Methods: The  methodological  approach  employed  in  this  study spanned from April 25, 2021, to May 5, 2021, and enlisted the participation of 347 nurses. Data collection was executed utilizing  a  “Personal  Information  Form”  and  the  “Quality Nursing Care Scale (QNCS).” The research comprised two phases: Phase 1 involved the adaptation of the scale, while Phase  2  focused  on  determining  construct  validity  through confirmatory  factor  analysis.  Reliability  was  assessed through  measures  of  internal  consistency  and  item-total correlation coefficients.Results and Discussion: The adaptation phase yielded affirmative outcomes, affirming the  linguistic  and  content  validation  of  the Turkish  version of  the  scale.  Confirmatory  factor  analysis  demonstrated  a highly favorable fit for a six-factor model. The Cronbach’s alpha  coefficient  for  the  entire  scale  was  determined  to  be 0.93, attesting to its strong internal consistency.Conclusion: The  Turkish  version  of  the  Quality  Nursing  Scale  showed consistently good psychometric properties of reliability and validity.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 826-833